Formulation of Public Policy Based on Islamic Legal Studies as a Solution in the Contemporary Era - Fakihudin, Rifki (Faculty of Law, Universitas Negeri Semarang, 2023)
In the contemporary era, the formulation of public policy faces multifaceted challenges, ranging from socioeconomic inequalities to cultural diversity and environmental sustainability. This paper explores the potential of Islamic legal studies as a framework for devising public policies that address these challenges while aligning with Islamic principles and values. By integrating insights from Islamic jurisprudence, ethics, and governance, this study elucidates how Islamic legal principles can inform the formulation and implementation of public policies that promote justice, equity, and welfare for all segments of society. Through a comprehensive review of relevant literature and case studies, this research examines the role of Islamic legal studies in shaping public policy across various domains, including economics, social welfare, environmental conservation, and governance. It analyzes the compatibility of Islamic legal principles with contemporary policy issues, highlighting areas of convergence and divergence with conventional policy approaches. Furthermore, this paper investigates the mechanisms for incorporating Islamic legal perspectives into the policymaking process, considering the roles of policymakers, scholars, civil society actors, and international institutions. The findings of this study contribute to the discourse on the role of Islamic legal studies in contemporary governance and policy development, offering insights into how Islamic principles can enrich and complement existing policy frameworks. By emphasizing principles of justice, compassion, and stewardship, policies informed by Islamic legal studies have the potential to address pressing societal challenges in a holistic and inclusive manner.